Enhancing Small and Medium Scale Enterprises Sustainability: Factors Influencing the Pottery Industry in Sri Lanka - Siriwardena, Buddhika Purnaka; Jathunarachchi, Sampath Sanjeewa; Vidanapathirana, Nisansala Priyadarshani (Talenta Publisher, 2023)
The pottery industry stands as a revered traditional handicraft, bearing both social and economic significance as a sustainable source of revenue within Sri Lanka. This study aims to unravel the elaborate factors that influence small and medium-scale enterprises (SMEs) within this industry. The study targeted small and medium-scale pottery producers in Udukiriwala, Hambantota District of Sri Lanka, with a sample size of 75 participants. The sampling technique employed was a simple random selection method. Data accumulation was coordinated via a precise pre-tested questionnaire, designed to encapsulate demographic particulars and inquiries connect to various constructs using a five-point Likert scale. Comprehensive statistical analysis ensued, encompassing mean calculations, standard deviations, correlation assessments, and regression analyses. Environmental factors exhibit a significant positive correlation, underlining their intense influence on the pottery industry's development. In absolute contrast, economic factors showcase a notable negative correlation. Meanwhile, sociological factors and government influence factors exhibit no statistically significant correlations with the pottery industry's evolution. The recognition of pivotal factors shaping the pottery industry sets the stage for well-informed actions, providing a solid basis for fostering its sustained expansion and advancement within the Sri Lankan context.